Hand dermatitis in beauticians in India - KHANNA, N (Indian journal of dermatology, venereology, and leprology, 1997)
One hundred and sixty-one beauticians and hairdressers (146 women and 15 men) were examined for the presence of hand dermatitis and those with hand eczema were patch tested with a battery of antigens standardised for beauticians. Forty-two (26.1%) subjects were found to have hand dermatitis and of these, in 31 (69.3%) the patch tests were positive; the following antigens elicited a positive response; paraphenylene diamine (35.5%), rubber antigens (22.6%), nickel (22.6%), shampoos (12.9%), ammonium thioglycollate (9.7%), ammonium persulphate (3.2%), henna mixture (3.2%) and detergents (6.5%). In addition, irritant reaction was seen in 7; in 5 patients it was to shampoos and in 2 to ammonium persulphate. Of the 8 patients who, on questioning, had a history of atopy, 7 (87.5%) had hand eczema, while 1 (12.5%) did not, and this difference was statistically significant (p < 0.001), suggesting that beauticians with a history of atopy were more likely to develop hand eczema.